2018
DOI: 10.1007/s12026-018-9017-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of MTHFR gene with smoking and alcohol use and haplotype combination susceptibility to psoriasis in Chinese population

Abstract: To investigate the association of MTHFR gene polymorphism and additional gene-gene interaction with psoriasis risk. GMDR model was used to screen the best gene-smoking and gene-drinking interaction combinations. Logistic regression was performed to investigate association between two SNPs and psoriasis. For psoriasis patient-control haplotype analyses, the SHEsis online haplotype analysis software ( http://analysis.bio-x.cn ) was employed. We found that carriers of homozygous mutant of rs1801133 polymorphism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Two previous meta-analyses were conducted, and no significant association of the MTHFR 677 C/T with the etiology of psoriasis was found [ 51 , 52 ]. It is necessary to update the data as many more studies appeared during the past years [ 31 , 42 , 44 , 45 , 53 ]. In this meta-analysis, we did not find any relationship of the SNP with psoriasis in overall comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous meta-analyses were conducted, and no significant association of the MTHFR 677 C/T with the etiology of psoriasis was found [ 51 , 52 ]. It is necessary to update the data as many more studies appeared during the past years [ 31 , 42 , 44 , 45 , 53 ]. In this meta-analysis, we did not find any relationship of the SNP with psoriasis in overall comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, inconsistent results were also observed. Kilic et al reported that the prevalence of the 1298 C allele was higher by 17.0-fold in patients with psoriasis compared to the control group [ 31 ], whereas Luo et al reported that the genotype distribution of the 1298 A/C was not different significantly between psoriasis patients and controls [ 42 ]. In this meta-analysis, although a significantly increased association of the CC and AC/CC genotypes was observed in Asians, there was no significant relationship between the 1298 A/C and psoriasis risk in overall analysis and Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…The association between MTHFR polymorphism and the susceptibility to psoriasis has been supported in Caucasians, Turkish, and Chinese populations ( 7 12 ). A study carried out in China reported that the rs1801133 T allele and the rs1801131 C allele were all associated with increased psoriasis risk ( 9 ). However, no studies have been found that surveyed the frequency of MTHFR polymorphisms in patients with PsA in the Han Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
“…e pathogenesis of psoriasis is still not completely clarified. Present studies have suggested that autoimmune disorders, dysfunction in various inflammatory signal transduction pathways, abnormal expression of psoriatic susceptibility gene, and obesity might be involved in the pathogenesis of psoriasis [3][4][5][6][7][8][9]. e unknown pathogenesis has brought difficulties to the treatment, without curative approaches against psoriasis at present.…”
Section: Introductionmentioning
confidence: 99%